Knowledge about veterinary anesthesia and the scope of anesthesiology for farmer - Debnath, Mira; Paul, Ashit Kumar (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The scope of anesthesiology is extended immensely. The aim of this study was to know the farmer’s understanding and scope of veterinary anesthesiology. Materials and method: A total of 155 data were collected from different Upazilla Livestock Office and Veterinary Hospitals during the period from July to December 2017 through interview with a pretested questionnaire. Farmer’s age, sex, educational status and occupation were considered during interview. Results: We found that 27.74% farmer had the experienced of their animal’s surgery whereas only 20% knew that anesthesia is given before surgery which is significantly (p<0.05) lower than that of disagree (48.39%).. Simultaneously 78.71% farmer did not know who gives the anesthesia and 76.77% do not believe that a vet doctor can anesthetize animals for surgery. Interestingly 51.61 % farmers have not any idea where veterinary surgeons regularly work. It is important to note that although 64.51% farmer thought that anesthetist is needed for surgery, however, there 66.45% don’t know the method of animal anaesthetization. In addition, 19.35% have little knowledge about anaesthesia. Finally we found 58.06% farmers (P<0.05) are interested to know about animal anesthesia if they get any opportunity to participate in a training program. Conclusion: Our data suggest that farmer’s understanding of animal anesthesia is very scanty. Therefore, planning and execution of basic awareness training program might capable to motivate farmers to bring their animal in a right place for the treatment. http://doi.org/10.5455/javar.2018.e277